2006
DOI: 10.3748/wjg.v12.i29.4694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca2+channel blockers on store-operated Ca2+channel currents of Kupffer cells after hepatic ischemia/reperfusion injury in rats

Abstract: SOC is the main channel for the influx of Ca(2+) during hepatic I/R injuries. Calcium channel blockers, 2-APB, SK and F96365, econazole and miconazole, have obviously protective effects on I/R injury, probably by inhibiting I(SOC) in Kupffer cells and preventing the activation of Kupffer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…The results suggest that carvacrol did not cause Ca 2+ influx via stored-operated Ca 2+ entry because carvacrol-induced Ca 2+ entry was not inhibited by three store-operated Ca 2+ entry blockers nifedipine, econazole and SK&F96365. These compounds have been widely applied as blockers of store-operated Ca 2+ entry in Kupffer cells (Ishikawa et al, 2003), T lymphocytes (Jiang et al, 2006) and glioblastoma cells (Hartmann and Verkhratsky, 1998). In the glioblastoma cells (DBTRG-05MG) used in this study, transient receptor potential melastatin 8 ion channels (TRPM8) was suggested to mediate the Ca 2+ entry induced by menthol (Wondergem et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that carvacrol did not cause Ca 2+ influx via stored-operated Ca 2+ entry because carvacrol-induced Ca 2+ entry was not inhibited by three store-operated Ca 2+ entry blockers nifedipine, econazole and SK&F96365. These compounds have been widely applied as blockers of store-operated Ca 2+ entry in Kupffer cells (Ishikawa et al, 2003), T lymphocytes (Jiang et al, 2006) and glioblastoma cells (Hartmann and Verkhratsky, 1998). In the glioblastoma cells (DBTRG-05MG) used in this study, transient receptor potential melastatin 8 ion channels (TRPM8) was suggested to mediate the Ca 2+ entry induced by menthol (Wondergem et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that thymol-induced Ca 2+ entry was inhibited with the three store-operated Ca 2+ entry blockers nifedipine, econazole and SK&F96365. Previous reports have suggested that these chemicals have been used as blockers of store-operated Ca 2+ entry in different cell models [30][31][32] . Because activation of phospholipase C produces inositol 1,4,5-trisphosphate and diacylglycerol, which activates protein kinase C, the effect of modulation of protein kinase C activity on thymolinduced [Ca 2+ ] i rise was examined.…”
Section: Discussionmentioning
confidence: 99%
“…The carvedilol-induced Ca 2þ influx seems to be mediated by a PKC -regulated Ca 2þ entry pathway that does not appear to be store-operated Ca 2þ channels or L-type Ca 2þ channels because the [Ca 2þ ] i rise was not inhibited by four blockers of storeoperated Ca 2þ entry: La 3þ , econazole, SKF96365, and nifedipine. [29][30][31][32][33] How carvedilol induced Ca 2þ influx is unclear. Evidence has shown that carvedilol appears to have a non-specific effect on membranes in phagocytes.…”
Section: Discussionmentioning
confidence: 99%